Features of immune status in athletes specializing in rowing and handball - V. S. Vasilenko; N. D. Mamiev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
The work is perfromed at the department of the hospital therapy GPMU, laboratory of llergiology and immunology of the research-practical Center of Dental faculty of SpbGMU named after I. Р. Pavlov. State of cellular and humoral immunity at the beginning and at the end of the training year of 15-17 years old young sportsmen of the first level and candidates masters of sports involved in an academic rowing and handball was studied. The athletes of both groups showed significant improvements as compared to the persons not involved in sports, lymphocyte apoptosis inducers (CD95+), the natural killer cells (CD16 + ) and B-lymphocytes (CD20 + ). Over time, in the athletes, regardless the sport, unidirectional changes are detected, encompassing the enhancing of the relative number of CD25+ with receptors for IL2, and immunoglobulin levels.